Cognitive Transformation Reflections Based on the Supply Chain Management and 5s Requirements (An Analytical Descriptive Study of a Sample of Workers in Zaki / Iraq Factory in the Province of Dohuk) - Alaa Aljalely; Manal Alsammak (International Journal of Supply Chain Management, 2019)
The organizations work in the face of competitive and environmental challenges that are intertwined and rapidly changing, as well as the information and technology revolution and the great development in all fields. These challenges require that these organizations should overcome the competition strategy of the logic of the cost to move to the strategy of competition in the logic of excellence in achieving their specific objectives. In this light the need for the use of new methods such as 5 s and supply chain managements by organizations are necessary. The importance of the study stems from the fact that it is related to the book's call for knowledge management to take into consideration the transformation of knowledge, which is linked to the philosophy of the five steps 5s in Zaki plant to achieve the production plan in time. The study is important in trying to provide a theoretical and field framework that links the transformation of knowledge and philosophy of the five steps 5s in the plant under study. In light of the problem of the study and its importance, the objective of the study is mainly to achieve the implications of cognitive transformation and knowledge of the ability to meet the requirements of 5s under study, the researchers considered that the transformation of knowledge independent variable and the philosophy of steps 5s adopted variable. The content of this research includes a description of the nature of the variables of the study as perceived by the individuals in the plant. To achieve this, (SPSS 19)* was used to deduce the computation, standard deviations, frequencies, percentages and response ratio to the area of the scale. The analysis of the data of this relationship was based on the hypothesis of the study, which states that